USING FIX-UP STRATEGY TO IMPROVE STUDENTS READING COMPREHENSION - Magfira, Magfira; Dewi, Anjar Kusuma (Universitas Muhammadiyah Makassar, 2024)
Fix-Up Strategy is an approach used in learning to help students overcome difficulties or confusion in understanding the material being studied. This strategy aims to help students improve or